The Impact of Monetary and Macroprudential Policies on Bank Risk-Taking: A Dynamic GMM Evidence from Indonesia - Suhendi Suhendi (Jurnal Ekonomi Pembangunan, 2025)
Instability in the banking sector can trigger a domino effect on the broader economy. Therefore, monitoring banks' risk-taking behavior is a crucial part of supervisory and economic policy development. This study aims to analyze how monetary and macroprudential policies influence banking risk-taking in Indonesia from 2015 to 2024. Financial stability is not solely determined by interest rate policy but also by macroprudential tools that help mitigate systemic risks. This research employs the System Generalized Method of Moments (GMM) with a sample of 33 commercial banks listed on the Indonesia Stock Exchange. The findings indicate that monetary policy (CBRATE) and macroprudential policy (MAPP) significantly impact banking stability, measured by the Z-score. When tested together, both policies work in a complementary manner, suggesting that coordinated policies can enhance the resilience of the financial system. Additionally, profitability (ROA) boosts bank stability, whereas exchange rate depreciation (ER) tends to undermine it. These results demonstrate that the synergy between monetary and macroprudential policies is vital for maintaining banking stability in Indonesia, particularly during global and post-pandemic periods.